2002
DOI: 10.1016/s0165-1765(02)00045-9
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in revealed risk taking: evidence from mutual fund investors

Abstract: Using data from a national survey of nearly 2000 mutual fund investors, we investigate whether investor gender is related to risk taking as revealed in mutual fund investment decisions. Consonant with the received literature, we find that women exhibit less risk-taking than men in their most recent, largest, and riskiest mutual fund investment decisions. More importantly, we find that the impact of gender on risk taking is significantly weakened when investor knowledge of financial markets and investments is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
275
1
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 469 publications
(302 citation statements)
references
References 3 publications
17
275
1
9
Order By: Relevance
“…A large experimental literature that compares how men and women value risky gambles or choose between gambles, documents systematic differences in risk preferences, with women being more risk-averse than men (see Croson and Gneezy (2009) and Eckel and Grossman (2008) for an extensive review of this literature). Higher risk-aversion of women is also reflected in financial decisions (Barber and Odean, 2001;Sapienza et al, 2009;Neelakantan, 2010), decisions made by financial professionals (Dwyer et al, 2002;Beckmann and Menkhoff, 2008) and even by top executives (Bandiera et al, 2015;Belenzon et al, 2016;Faccio et al, 2016). Higher risk-aversion of women is often explained by their relatively lower overconfidence (Lundeberg et al, 1994;Barber and Odean, 2001).…”
Section: H1mentioning
confidence: 99%
“…A large experimental literature that compares how men and women value risky gambles or choose between gambles, documents systematic differences in risk preferences, with women being more risk-averse than men (see Croson and Gneezy (2009) and Eckel and Grossman (2008) for an extensive review of this literature). Higher risk-aversion of women is also reflected in financial decisions (Barber and Odean, 2001;Sapienza et al, 2009;Neelakantan, 2010), decisions made by financial professionals (Dwyer et al, 2002;Beckmann and Menkhoff, 2008) and even by top executives (Bandiera et al, 2015;Belenzon et al, 2016;Faccio et al, 2016). Higher risk-aversion of women is often explained by their relatively lower overconfidence (Lundeberg et al, 1994;Barber and Odean, 2001).…”
Section: H1mentioning
confidence: 99%
“…In general, there is a consensus among researchers that women are less inclined towards risk taking than men [38,39] and that men behave less carefully and undertake more risky strategies than women in their fund's investment decisions [40,41]. Research conducted by Olsen and Cox [42] among professional investors also revealed that women are more interested in steady returns from investments while men are strongly focused on increasing profits.…”
Section: Esg and Protection Against The Riskmentioning
confidence: 99%
“…Sundén and Surette, 1998;Barber and Odean, 2001;Dwyer, Gilkeson, and List, 2002;Agnew, Balduzzi, and Sundén, 2003). Compared to men, women are more risk-averse (e.g., Barsky et al, 1997; for reviews see Eckel and Grossman, 2008;Croson and Gneezy, 2009) and score lower in financial literacy tests (Chen and Volpe, 2002;Lusardi and Mitchell, 2008).…”
Section: Introductionmentioning
confidence: 99%